Evaluated of Death Penalty Given During The Period of Sultan Abdulhamit II - Aksın, Ahmet (Fırat University, 2021)
After the Tanzimat Period in the Ottoman State if the crime was commited in İstanbul, the trial would carried out in fatwa house, if it was committed in rural the trial would carried out (state) parliament, the judge provision would be sent to the rural again by padishah consent after the examination of the fatwa house, would talion executed. As for talion book is notebooks that saved of resolutions belong to execution these given punishments. In the Prime Ministry State Archives there are 10 pieces books containing the punishment records of between the dates H.1256-1327 / AD. 1840-1903 registered in the “Catalog of Imperial Council Books” number 989 series of Banishment and Trial books. In the Talion Books the state that has given punishments for these criminals with taken place quarrel, latrocination, seizure, banditry, receivables, economic competition, escape etc. by reason of commit murders and crimes. In our communique, were made evaluated of 130 pieces judgments 104-184 between the pages (1876-1908) belong to the period of Sultan Abdülhamit II number 10 book of talion which inclusive years of 1874-1903. By evaluating these documents; crime and crime rates with cities where the events took place crime, political crimes (committism, state to revolt, etc.) committed at the events, with the reasons for the committed murders (honor, receivables and payables, hostility, etc.) the numbers and rates of men, women, children on the basis of killer and victim, in murder committed were tried to revealed Muslim- Nonmuslim numbers and rates.

Osmanlı Devleti’nde Tanzimat’tan sonra suç İstanbul’da işlenmiş ise yargılama Fetvahane’de, taşrada işlenmiş ise memleket (eyalet) meclisinde yapılacak, yargı hükmü Fetvahane ‘nin incelemesinden sonra padişah onayladıysa, tekrar taşraya gönderilip, kısas infaz edilecekti. Kısas Defterleri ise bu verilen cezalarının icrasına ait hükümlerin kaydedildiği defterlerdir. Cumhurbaşkanlığı Devlet Arşivinde Nefy ve Kısas defterleri serisinden 989 numaralı "Divân-ı Hümayun Defterleri Kataloğunda kayıtlı H.1256–1327 / M. 1840–1903 tarihleri arasındaki ceza kayıtlarını ihtiva eden 10 adet defter vardır. Kısas Defterlerinde meydana gelen münakaşa, yol kesme, gasp, eşkıyalık, alacak, ticari rekabet, firar, vs. sebeplerle işlenen cinayetler ve suçlar ile devletin bu suçlulara vermiş olduğu cezalar yer almaktadır . Çalışmamızda 1874-1903 yıllarını ihtiva eden 10 Numaralı Kısas Defteri’nin Sultan II. Abdülhamit dönemine ait (1876-1908) 104-184. sayfaları arasındaki 130 adet hükmün değerlendirilmesi yapılmıştır. Bu belgeler değerlendirilerek; olayların meydana geldiği şehirler ile suç ve suç oranları, olaylarda işlenen siyasi (komitacılık, devlete başkaldırı, vs.) suçları, işlenen cinayetlerin sebepleri (namus, alacak verecek, husumet vs. ile katil ve maktul bazında erkek, kadın, çocuk sayıları ve oranları, işlenen cinayet suçlarında Müslim-Gayrimüslim sayıları ve oranları ortaya konulmaya çalışılmıştır.
SULTAN II. ABDÜLHAMİT DÖNEMİ ÖLÜM CEZALARININ DEĞERLENDİRİLMESİ (1876-1908)